Empboard (International Journal of Engineering and Computer Science, 2017)
EMPBOARD is the process of employee recruitment in an efficient way so as to make it a steamroll for the employee, reduce risk and provide maximum benefits by e-provisioning. An employee’s paperwork is not sufficient to meet today’s requirement. EMPBOARD offers employees a comprehensive benefits package. EMPBOARD allows in pleasing all the requirements and make the enterprise run efficiently. With the concept of e-Provisioning coming in, the agencies undertake or build gear to begin the method while a brand new worker is employed. Worker becoming a member of the company is a big occasion now not only for a worker who is joining however similarly for the HR and the associated features that have the duty to ensure the worker isn't sitting idle due to loss of sources. The procedure is supported via the get admission to a management application that automates maximum of the work, saving time and not requiring the intervention of community directors or mainframe operators.